Inovasi Pembelajaran Pai Di Era Digital: Pengembangan Video Animasi Interaktif Sebagai Media Edukatif - Bula, Rizqah Fadhilah; Supiah (Jurnal Pustaka Cendekia Pendidikan, 2025)
This study aims to examine the innovation of Islamic Religious Education (PAI) learning in the digital era through the development of interactive animation videos as an educational medium. The research method applied is library research with a descriptive qualitative approach. Data were collected through literature reviews from various academic sources, including books, scientific journals, and relevant research articles. The findings indicate that the use of interactive animation videos can enhance students' understanding of abstract concepts in PAI, motivate learners, and improve their learning outcomes. Additionally, this medium contributes to creating a more engaging, interactive, and contextual learning experience tailored to the needs of today's digital generation. However, the implementation of this medium still faces challenges, such as limited digital infrastructure, low digital competence among teachers, and restricted access to technology in certain schools. Therefore, policy support, teacher training, and collaboration between educational institutions and technology developers are needed to optimize interactive animation videos as an innovative and effective learning medium in Islamic Religious Education. With proper integration, this approach is expected to positively impact the quality of Islamic education and address the challenges of learning in the digital era.